TINGKAT KELAYAKAN LAHAN TPA SAMPAH KOTA MANADO DALAM UKURAN MITIGASI PERENCANAAN LOKASI TPA - Zetly Tamod (EKOTON, 2013)
The important function must be paid attention in waste management is landfill. At the location, the collected waste must be isolated well for not making new problem for surrounding environment. The existing of appropriate landfill location plan can minimize waste impact. This research was conducted at Sumompo landfill waste area of Manado Town by using survey method. Analysis variable of bio-geophysical referenced to SNI 03-3241-1991 adjusting SNI 03-324–1994 and was conducted standardization by dividing suitableness class of land is very suitable (good category), suitable enough (middle category), and less suitable (poor category). Analysis of social condition was conducted by viewing various response respondent level for existence of landfill location, then it was conducted standardization with dividing people response level become positive, neutral and negative. The result research, adequacy level of waste landfill Manado town in measurement of mitigation plan for landfill location is categorized suitable enough (middle category). The assessment is based on geophysical land review including suitable enough (middle category). The assessment was based on geophysical review of land including suitableness class II. For people encouragement was based on indicator of landfill existence, in neutral tend to positive (neutral category by Mahawu and Buha accepting by Tumintang, Sumompo, and waste collector).